Flavoprotein-Mediated Tellurite Reduction: Structural Basis and Applications to the Synthesis of Tellurium-Containing Nanostructures - Arenas-Salinas, Mauricio; Vargas-Pérez, Joaquín I.; Morales, Wladimir; Pinto, Camilo; Muñoz-Díaz, Pablo; Cornejo, Fabián A.; Pugin, Benoit; Sandoval, Juan M.; Díaz-Vásquez, Waldo A.; Muñoz-Villagrán, Claudia; Rodríguez-Rojas, Fernanda; Morales, Eduardo H.; et al. (Frontiers in Microbiology, 2016)
The tellurium oxyanion tellurite (TeO32-) is extremely harmful for most organisms. It has been suggested that a potential bacterial tellurite resistance mechanism would consist of an enzymatic, NAD(P)H-dependent, reduction to the less toxic form elemental tellurium (Te0). To date, a number of enzymes such as catalase, type II NADH dehydrogenase and terminal oxidases from the electron transport chain, nitrate reductases, and dihydrolipoamide dehydrogenase (E3), among others, have been shown to display tellurite-reducing activity. This activity is generically referred to as tellurite reductase (TR). Bioinformatic data resting on some of the abovementioned enzymes enabled the identification of common structures involved in tellurite reduction including vicinal catalytic cysteine residues and the FAD/NAD(P)+-binding domain, which is characteristic of some flavoproteins. Along this line, thioredoxin reductase (TrxB), alkyl hydroperoxide reductase (AhpF), glutathione reductase (GorA), mercuric reductase (MerA), NADH: flavorubredoxin reductase (NorW), dihydrolipoamide dehydrogenase, and the putative oxidoreductase YkgC from Escherichia coli or environmental bacteria were purified and assessed for TR activity. All of them displayed in vitro TR activity at the expense of NADH or NADPH oxidation. In general, optimal reducing conditions occurred around pH 9-10 and 37 °C. Enzymes exhibiting strong TR activity produced Te-containing nanostructures (TeNS). While GorA and AhpF generated TeNS of 75 nm average diameter, E3 and YkgC produced larger structures (> 100 nm). Electron-dense structures were observed in cells over-expressing genes encoding TrxB, GorA and YkgC.